Child health: The importance of breastfeeding in preventing overweight and obesity in childhood (Research, Society and Development, 2024)
Introduction: Breast milk is the ideal food for babies and should be offered exclusively for six months, and after the introduction of solid foods until at least two years. In addition to providing all the nutrients necessary for healthy growth and development, it plays a fundamental role in several disease prevention, including overweight and obesity. Objective: To analyze the importance of breastfeeding in childhood overweight prevention and obesity. Methods: A quantitative descriptive study was conducted, in which several scientific sources were analyzed to understand the relationship between breastfeeding practice and the prevention of childhood excess weight. The research is based on studies that demonstrate the impact of the nutritional, and immunological of breast milk, highlighting how it contributes to healthy development and weight control throughout childhood. Discussion: The results of this literature review show that breastfeeding is one of the most important factors in childhood obesity prevention and overweight. Although other factors, such as genetics and the environment, also influence the development of obesity, the benefits of breastfeeding are undeniable. The unique composition of breast milk, the mother-infant interaction during breastfeeding, and the modulation of the intestinal microbiota are mechanisms proposed to explain this association. Given the evidence presented, promoting exclusive breastfeeding in the first six months of life and continuing until two years of age or beyond should be a priority in public health policies. Final considerations: Breastfeeding is essential to reduce the risks of childhood overweight and obesity. The benefits of breast milk go beyond nutrition, enabling a healthy foundation for growth and strengthening immunity, factors that help prevent future chronic conditions, such as obesity.